The Ideal of a Catholic Education in a Secularized Society - Cuypers, Stefaan E. (Catholic Education: A Journal of Inquiry and Practice, 2004)
This paper argues that the progressive, revisionist reaction within Catholic education and schooling, as well as within Catholicism at large, to the challenge of modernity is a mistake. In view of modernity’s malaises, it advocates instead the affirmation or reaffirmation of the ideal of traditional Catholicism as the only authentic response for Catholics to modern progress. In order to justify the distinctiveness of a traditional Catholic identity and educational project, the paper offers an outline of a distinctively Thomistic educational philosophy. Its defense of the (re)affirmation of the ideal of traditional Catholic education and schooling in secularized society is neither ultra-conservative nor romantic.